SYSTEMIC FAILURES IN MEDICAL EDUCATION GOVERNANCE: THE 2024 MDCAT SCANDAL IN KARACHI, PAKISTAN (Journal of Medical & Health Sciences Review, 2025)
The study critically evaluates the systemic institutional failures in medical education governance in Pakistan in the context of the 2024 Medical and Dental College Admission Test (MDCAT) scandal that took place in Karachi, Pakistan. As a qualitative case study, evidence from forensic materials, case law, media reports, and stakeholder interviews was triangulated to reveal significant failures in the exam's institutional integrity, due diligence, and compliance. It was evident that the exam paper had been leaked and impersonated by central institutions, including IBA, NED University, and DUHS. The paper discusses the broader implications of these failures on trust, meritocracy, and healthcare quality and offers evidence-based recommendations for institutional and regulatory reform.